Regional Connection under the Belt and Road Initiative The Prospects for Economic and Financial Cooperation - Cheung, Fanny M.; Hong, Ying-yi (Routledge Studies on Asia in the World, 2019)
China's Belt and Road Initiative (BRI) is intended to radically increase investment and integration along a series of land and maritime routes. As the initiative involves more than 100 countries or international organizations and huge amounts of infrastructure construction, cooperation between many different markets is essential to its success. Cheung and Hong have edited a collection of essays that, between them, examine a range of practical issues facing the BRI and how those issues are being addressed in a range of countries. Such challenges include managing financing and investment, ensuring infrastructure connectivity, and handling the necessary e-commerce and physical logistics. Emphasizing the role of Hong Kong as an intermediary and enabler in the process, this book attempts to tackle the key practical challenges facing the BRI and anticipate how these challenges will affect the initiative's further development. The book provides a holistic and international approach to understanding the implementation of the BRI and its implications for the future economic integration of this huge region.